The Relationship of Gender, Gender-Related Traits, and Achievement Orientation to Achievement Attributions: A Study of Subject-Selected Accomplishments - Gaeddert, William P. (Journal of personality, 1987)
ABSTRACT Female and male college students (N= 251 and 84, respectively) described important accomplishments in their lives and reported attributions for the causes of their success Regression analyses indicated that, as predicted, students' gender explained a small portion of the variance in attributions, and the goals and performance standards of the students' achievement experiences (achievement orientations) accounted for more variance in attributions than did the other predictors Further analyses showed that the domains of students' accomplishments affected their attributions to effort luck, and ability, and that students' achievement goals and performance evaluation standards predicted their attributions to task difficulty, effort, and ability Researchers are urged to explore attributions made concerning self‐selected achievements, and to focus on variables other than sex in their search for the determinants of achievement attributions